2018
DOI: 10.1029/2018jd028697
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Sea Ice Melt Onset and Retreat in the Laptev Sea by the Timing of Snow Retreat in the West Siberian Plain

Abstract: Recent years have seen growing interest in improving seasonal predictions of Arctic sea ice conditions, including the timing of ice melt onset and retreat, especially on the regional scale. This paper investigates potential links between regional sea ice melt onset and retreat in the southern Laptev Sea and retreat of terrestrial snow cover. Past studies have shown that variability of snow extent over Eurasia can substantially impact regional atmospheric circulation patterns over the North Pacific and Arctic O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 52 publications
2
20
0
Order By: Relevance
“…In general, low pressure over Eurasia and high pressure over the central Arctic or North America often lead to the initiation of melt onset, particularly in the Laptev, East Siberian, Chukchi, and Beaufort seas. Previous work has found that this pressure pattern can be triggered by snow retreat in Eurasia (Crawford et al 2018;Matsumura et al 2014): As snow cover melts, the surface warms due to reduced surface albedo, amplifying stationary Rossby waves and leading to a deceleration of the polar jet (Matsumura et al 2014). This produces negative SLP anomalies over Eurasia and positive anomalies in the central Arctic, variations of which appear on the right side of the master SOM (Fig.…”
Section: Discussionmentioning
confidence: 96%
“…In general, low pressure over Eurasia and high pressure over the central Arctic or North America often lead to the initiation of melt onset, particularly in the Laptev, East Siberian, Chukchi, and Beaufort seas. Previous work has found that this pressure pattern can be triggered by snow retreat in Eurasia (Crawford et al 2018;Matsumura et al 2014): As snow cover melts, the surface warms due to reduced surface albedo, amplifying stationary Rossby waves and leading to a deceleration of the polar jet (Matsumura et al 2014). This produces negative SLP anomalies over Eurasia and positive anomalies in the central Arctic, variations of which appear on the right side of the master SOM (Fig.…”
Section: Discussionmentioning
confidence: 96%
“…Though not commonly used in sea ice applications, Brown et al (2014) show that IMS is advantageous over several automated algorithms for monitoring sea ice phenology. IMS is also able to improve sea ice estimates by reducing land contamination and better representing coastal regions compared to passive microwave estimates (Brown et al, 2014), as well as to resolve finer-scale details between narrow ocean channels (Dauginis and Brown, 2020). This work expands on the work of Dauginis and Brown (2020) and examines changes in sea ice, lake ice, and snow phenology from 1997-2019 across the pan-Arctic.…”
Section: Introductionmentioning
confidence: 93%
“…The Canadian Arctic Archipelago (CAA), however, has been shown to exhibit earlier freeze trends during recent years (e.g. Dauginis and Brown, 2020) and weaker trends toward earlier melt onset compared to other Arctic regions (e.g. Mahmud et al, 2016;Marshall et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CC BY 4.0 License. Lynch et al 2017;Crawford et al 2018). Passive microwave data are well-suited for snow and ice monitoring due to allweather imaging capabilities and long available records (since the late 1970s), though the coarse resolution (25 km) limits their application and reduces the accuracy of estimates (Derksen et al 2004;Gao et al 2010;De Lannoy et al 2012).…”
Section: Introductionmentioning
confidence: 99%